HUMAN TERATOGENESIS: GENE–ENVIRONMENT INTERACTION AND FOUNDATIONS FOR PREVENTION - Vargas-Vera, Ramón Miguel; Placencia-Ibadango, Martha; Flores-Luna, Ana María; Alencastro-Placencia, Saúl Alexander; Gunsha-Aguilar, Jorge Luis; Campos-Carbo, Lito Danny; Vargas-Silva, Kalid Stefano; Palacios-Távara, María del Socorro (Seven Editora, 2026)
Human teratogenesis is a complex process resulting from the interaction between environmental factors and maternal–fetal genetic susceptibility, capable of altering embryofetal development and producing structural, functional, and neurodevelopmental anomalies. The vulnerability of the embryo and fetus depends on the timing of exposure, with organogenesis (weeks 3–8) being the period of highest risk for major malformations, whereas in later stages functional and growth alterations predominate. The principles of teratology, described by Wilson, establish that the teratogenic effect is conditioned by dose, duration of exposure, genetic susceptibility, and the pathogenic mechanisms involved, such as oxidative stress, DNA damage, altered cell proliferation, and disruption of angiogenesis. Teratogenic agents are classified as biological, physical, chemical, and maternal factors, all with convergent mechanisms that affect fetal development. Biological teratogens include congenital infections that cause damage through direct invasion and inflammation. Physical agents, such as ionizing radiation and hyperthermia, produce cellular and structural alterations. Chemical agents, including drugs, alcohol, tobacco, and environmental pollutants, interfere with key molecular processes and represent a frequent cause of preventable fetal damage. Maternal factors, such as diabetes, phenylketonuria, and nutritional deficiencies, modify the intrauterine environment. Early recognition of risk exposures and the implementation of preventive strategies are essential to reduce the incidence of congenital anomalies and improve perinatal outcomes.